2009
DOI: 10.1002/elan.200904583
|View full text |Cite
|
Sign up to set email alerts
|

Adsorptive Stripping Voltammetric Determination of Nanomolar Concentration of Cerium(III) at a Carbon Paste Electrode Modified by N′‐[(2‐Hydroxyphenyl)Methylidene]‐2‐Furohydrazide

Abstract: The aim of this work was to obtain an adsorptive stripping voltammetric method for the Ce(III) determination at a carbon paste electrode, chemically modified with N-[(2-hydroxyphenyl)methylidene]-2-furohydrazide (NHMF). The electroanalytical procedure comprised two steps: the Ce(III) chemical accumulation at À 200 mV followed by the electrochemical detection of the Ce(III)/NHMF complex, using anodic stripping voltammetry. The factors, influencing the adsorptive stripping performance, were optimized including t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 25 publications
1
7
0
Order By: Relevance
“…The stripping peaks and detection limits for Ce(III) were very good, when compared with other voltammetric methods in existence. The detection limits compared well with studies obtained elsewhere [32,36,37]. Most researchers have found it difficult to produce discrete La(III) and Pr(III) analysis by voltammetric methods [38,39].…”
Section: Site Id Metal Ionssupporting
confidence: 76%
See 1 more Smart Citation
“…The stripping peaks and detection limits for Ce(III) were very good, when compared with other voltammetric methods in existence. The detection limits compared well with studies obtained elsewhere [32,36,37]. Most researchers have found it difficult to produce discrete La(III) and Pr(III) analysis by voltammetric methods [38,39].…”
Section: Site Id Metal Ionssupporting
confidence: 76%
“…However, NO 3 interfered significantly with the REEs than PO 4 and SO 4. Separation techniques before voltammetric analysis may overcome this problem, as reported elsewhere [32]. Tables 3 and 4 show the results obtained from the voltammetry and ICP-OES techniques, respectively.…”
Section: Dpadsv Analysismentioning
confidence: 98%
“…Recently, we used modified CPEs for trace analysis of some drugs and heavy metals in various environments [20][21][22][23][24]. Newly we showed that the application of nanopowders of Fe 2 TiO 5 in CPEs catalyses the oxidation of salbutamol and enhances the peak current values in the differential pulse anodic stripping voltammetric (DPASV) determination of it at sub-nanomolar levels [25].…”
Section: Introductionmentioning
confidence: 99%
“…For cerium determination, the deposition potential re-quired is too negative to be detected by ASV, as the standard reduction potential for the Ce 3 + /Ce 0 redox couple is À2.48 V. This can be a challenge for most electrode materials, including ITO, because of inadequate hydrogen overpotential resulting in significant interference from hydrogen gas bubbles reducing the effective electrode surface area. Mehran et al used AdSV on a carbon paste electrode modified with N'-[(2-hydroxyphenyl)methylidene]-2-furohydrazide (NHMF), and achieved a detection limit of 0.8 nM [32]. While this novel sensor only required a response time of ca.…”
Section: Introductionmentioning
confidence: 99%
“…Abbas et al used a novel potentiometric sensor composed of a new nano-composite carbon paste electrode fabricated from (Z)-2-((1H-1,2,4-triazol-3ylimion)methyl)phenol, as an ionophore, a multiwalled carbon nanotube (MWCNT), nanosilica, and air and water-stable ionic liquid [BMP]Tf 2 N for the quantification of cerium(III) ions and achieved a detection limit of 6.45 nM [31]. A disadvantage of AdSV is the need to use an organic ligand for complexing the analyte, the use of a mercury electrode, which is a requirement of many adsorptive stripping procedures [23], or the use of more complicated modified carbon paste electrodes like the ones already mentioned [32]. 5 s and gave good selectivity, the requirement of a combination of reagents for modification of a carbon paste electrode makes it less attractive because of the lengthy electrode preparation.…”
Section: Introductionmentioning
confidence: 99%